Identifying key barriers to nonprofit organizations' adoption of technology innovations - Godefroid, Marie‐E; Plattfaut, Ralf; Niehaves, Björn (Nonprofit management & leadership, 2024)
Despite substantial innovations in Information and Communication Technologies (ICT) that could benefit non‐governmental organizations (NGOs), NGOs are not using ICT yet to their full potential – especially compared to the ICT use in the private sector. Such behavior appears counterintuitive as one would expect NGOs to use every available resource to further their important mission. However, reservations appear to remain even though several case studies demonstrated the value ICT can generate for NGOs. Through a series of 20 interviews with NGOs of various sizes and backgrounds, we examined the use of ICT along the NGO value chain (program design, fundraising, fund management, and program delivery). We find a distinct prioritization of ICT support along the value chain. Based on these findings, we identify six sector‐specific reasons for NGOs not to use ICT for certain activities. With these, we add to known reasons in the literature and offer important avenues for further research.